2022
DOI: 10.2174/0929867328666210827102456
|View full text |Cite
|
Sign up to set email alerts
|

Feruloyl Sucrose Esters: Potent and Selective Inhibitors of α-glucosidase and α-amylase

Abstract: Introduction: Feruloyl Sucrose Esters (FSEs) are a class of Phenylpropanoid Sucrose Esters (PSEs) widely distributed in plants. They were investigated as potential selective Alpha Glucosidase Inhibitors (AGIs) to eliminate the side effects associated with the current commercial AGIs. The latter effectively lowers blood glucose levels in diabetic patients but causes severe gastrointestinal side effects. Methods: Systematic structure-activity relationship (SAR) studies using in silico, in vitro and in vivo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…The study also identified O-3 substituents as favorable for increased level of inhibition of α-glucosidase [6,9,10]. Additionally, the di-isopropylidene bridges favorably reduce the inhibition of α-amylase and minimally affect the inhibition of α-glucosidase [6,9,10]. These results were further corroborated by silico docking and molecular modelling studies.…”
Section: Introductionmentioning
confidence: 87%
See 3 more Smart Citations
“…The study also identified O-3 substituents as favorable for increased level of inhibition of α-glucosidase [6,9,10]. Additionally, the di-isopropylidene bridges favorably reduce the inhibition of α-amylase and minimally affect the inhibition of α-glucosidase [6,9,10]. These results were further corroborated by silico docking and molecular modelling studies.…”
Section: Introductionmentioning
confidence: 87%
“…The side effects hamper patient compliance and acceptability, and limit the wide use of these effective drugs [13]. Based on a preliminary structure-activity relationship (SAR) study [6,9,10], we demonstrated that their in vitro inhibition of α-glucosidase and α-amylase depended on the type, number, and position of the phenylpropanoid moieties on the sucrose core and the presence/absence of the di-isopropylidene bridges (Figure 1). The study also identified O-3 substituents as favorable for increased level of inhibition of α-glucosidase [6,9,10].…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…This is specifically important to study the structure-activity relationships (SARs) of these compounds to develop lead drug candidates. 32 Our earlier investigation of PSEs as potential antidiabetic lead candidates proved that the type, number, and position of the (substituted) cinnamoyl moieties greatly impact the a-glucosidase and a-amylase inhibition activities. 32 In particular, the moieties at O-3, O-3 0 , O-4 0 , and O-6 0 play a critical role in the inhibition.…”
Section: Introductionmentioning
confidence: 99%